Marginal Regions in Discursive Space: An Examination of Socio-economic Conditions, Development Paths and Spatial Differentiation in the Economic Systems of the Canadian and Russian North - Petrov, Andrey
Marginal regions in discursive space: an examination of socio-economic conditions, development paths and spatial differentiation in the economic systems of the Canadian and Russian North Andrey N Petrov Degree: Doctor of Philosophy Department of Geography University of Toronto 2008 This dissertation is an effort to provide a new insight into the problem of regional development in remote areas under changing global and national political and economic conditions. It undertakes an assessment of shared economic histories, recent changes and future possibilities of socioeconomic prosperity and sustainability in marginal regions of Canada and Russia. The first chapter re-examines the structure of Canada’s and Russia’s space-economies by evoking the concept of regional multichotomies and economic marginality. I consider whether outcomes, geographic patterns and spatial logics of regional differentiation in the two countries are similar and explore the evidence of similarity between the North(s). Finding development outcomes in the Russian and Canadian North strikingly similar, the second chapter uses a combination of discursive analysis and regulation theory to re-interpret the origins of present-day problems and examine the genealogy of northern development. It argues that the Canadian and Russian northern development regimes shared profound commonalities. From these positions, the chapter compares and critiques past and present policies of regional development in the two Norths, and discusses their viability. The third chapter dwells upon a concept of ‘development regimes’ to analyze and compare contemporary regional development policies. It further investigates how recent economic development policies in the two Norths are adapting to changing economic and political realities, and if they were able to deliver desirable results to northern communities. The chapter compares and critiques contemporary policies and discusses possible alternative perspectives that reconcile an emerging postcolonial paradigm of development and realities of post-Fordism. It introduces the notion of the neo-staple development regime and describes its manifestations (Impact and Benefit Agreements). The fourth chapter presents a case for fostering knowledge based development and creative capital in the North. It builds on the innovation systems and institutional geography literatures to argue that the creative capital in the periphery is a pivotal factor of regional development. The chapter provides a conceptualization and empirical analysis of the creative class in remote regions. Contrary to the metropolitan bias, I argue that creative ‘hot spots’ beyond metropolis exist, and could become the centres of regional reinvention, if appropriate policies are introduced in support. PhD